Transforming Academic Identity Through Smart Pedagogy and Digital Storytelling in Higher Education - Dipangshu Dev Chowdhury; Nabaraj Bhowmik (Journal of Smart Pedagogy and Education, 2026)
This research explores the transformation of academic identity and smart pedagogy within higher education during the digital era. It focuses on integrating digital storytelling, inclusivity, and community service to enhance learning outcomes and institutional relevance. As digital technologies redefine educational boundaries, academics must adapt their professional identities to incorporate innovative pedagogical approaches. Digital storytelling serves as a vital tool for fostering engagement and critical thinking, while inclusivity ensures equitable access for diverse student populations. Furthermore, the integration of community service bridges the gap between theoretical knowledge and practical societal impact. By examining these core components, the study highlights how smart pedagogy creates a more responsive and ethically grounded academic environment. The findings suggest that a holistic integration of digital tools and social responsibility is essential for modern universities to thrive. Ultimately, this transformation empowers both educators and students to navigate the complexities of a technology-driven global landscape effectively and inclusively.